Clinical evaluation of toll-like receptor-5 agonist for radiation-induced oral mucositis in beagle dogs - Ko, Jaeeun; Kim, Jaehwan; Choi, Yang-Kyu; Nahm, Sang-Soep; Kim, Jayon; Seo, Sun-Min; Seo, Jin-Seok; Lee, Woojong; Chung, Weon Kuu; Eom, Kidong (Frontiers in Veterinary Science, 2022)
The aim of this study was to evaluate the clinical safety and validate the radiomitigative effect of KMRC011, against radiation-induced oral mucositis in beagle dogs. Clinical safety was evaluated by assessing tolerability, complete blood tests, plasma biochemistry after drug administration. The radiomitigative effect of KMRC011 was evaluated based on the macropathological, histopathologically after inducing oral mucositis iatrogenically using 20 Gy irradiation. The plasma concentration of interleukin-6 was measured via enzyme-linked immunosorbent assay, as a biomarker of KMRC011 bioreactivity. Decreased tolerability, increased neutrophil count, hepatic enzyme, C-reactive protein and interleukin-6 after the administration was observed and ceased within 24 h without additional treatment. Although all animals included in the present study developed severe mucositis in the late course of the study, animals administered KMRC011 showed less erythema, ulcer, inflammatory infiltration and pain. These results suggest that KMRC011 may be used as an adjuvant for radiotherapy without severe adverse effects, especially during short-term RTx such as stereotactic RTx or radiosurgery.